Characterization of Mechanical Damage to the Aorta in Hypoxic Condition Numerical Modeling and Simulation of a Pressurization Test - Garcia-Herrera, C; Rivera-Mancilla, E; Bezmalinovic-Colleoni, A (UNIV FED RIO DE JANEIRO, LAB HIDROGENIO, 2021)
In order to reliably assess the rupture-risk of the aorta - along with the hazardousness index of cardiovascular diseases or other extreme conditions, and the effect of possible treatments - it is necessary to know the damage mechanisms that lead to it. In this work, the mechanical damage of hypoxic aortic tissue is characterized, numerically predicting its response when subjected to a bulge-test type of pressurization state. The mechanical behavior of the aortic wall, is described using a hyperelastic material model with two transverse-isotropy directions and an isotropic damage model; both experimentally calibrated, from previously reported uniaxial tensile-test results, performed on thoracic aorta samples of lambs exposed to chronic hypobaric hypoxia. A melatonin-treated group is studied in contrast to a control group. Once the constitutive model is calibrated, its performance is evaluated via the numerical simulation of the bulge-pressurization test; in which the quasistatic response of a quarter-disk shaped structure, fixed along its curved perimeter, and loaded out of its plane by a pressure, or force per unit area permanently normal to the loaded area, its analyzed. The experimental data and the results of numerical simulations indicate that a melatonin treatment reduces the stiffness of the aorta. Moreover, the group-wise determined pressures, delivered by the bulge-test simulation and associated with the onset of damage, are compatible with an arterial hypertensive condition.